From Simulation to Competence: Examining the Impact of Virtual Reality Training on Aspiring Heavy Equipment Mechanics - Arga Kuncoro Jati; Sutiman (Universitas Pendidikan Ganesha, 2025)
Excavators play a crucial role in Indonesia’s mining industry; however, the growing demand for competent mechanics has not been matched by the quality of training, posing risks to both productivity and workplace safety. Virtual Reality (VR) offers a realistic, safe, and effective training method to enhance such competencies. This study employed a quasi-experimental pretest-posttest control group design involving 60 participants in a maintenance small excavator training program at UT School Jakarta, randomly assigned to a control group (conventional method) and an experimental group (VR) for a total of 32 instructional hours. Pretest results indicated comparable initial competencies, while posttest results revealed a significant improvement in the experimental group (t = -6.116; p < 0.05) with an N-Gain of 0.73 (high category) compared to the control group’s 0.58 (medium category). These findings confirm VR’s effectiveness in improving technical understanding, maintenance skills, and work attitudes through immersive simulations aligned with the Indonesian Heavy Equipment Competency Scheme standards. The novelty of this study lies in the direct application of VR to the small excavator maintenance cluster in Indonesia, recommending the integration of this technology into vocational curricula to bridge competency gaps in the heavy equipment industry.